The effects on waste stabilization of leachate recirculation in landfills - Demir, A; Özkaya, B; Bilgili, MS (Parlar Research & Technology UG, 2004)
In this study, the effects of leachate recirculation (LR) on waste stabilization are evaluated at the test area and field scale test cells, both of which are located in the European side of Istanbul. The test area is an inactive part (1.5 ha) of Odayeri Sanitary Landfill (OSL). The dimensions of the test cells, of which one is wet-cell due to the LR application and the other is not, are 25x50x5m. In this paper, methane content and quantity of landfill gas (LFG) is evaluated as stabilization indicator. It is determined that the methane quantity of LFG is increased by about 10% in the test area, reached 220 days earlier to methane phase at wet-cell by LR application. According to results obtained from the test studies, it is concluded that LR application enhances waste stabilization.
Keywords: LFG; leachate; methane; recirculation; test cells; waste stabilization; MUNICIPAL SOLID-WASTE; Environmental Sciences & Ecology